2020
DOI: 10.1177/2381468320933576
|View full text |Cite
|
Sign up to set email alerts
|

“Along for the Ride”: A Qualitative Study Exploring Patient and Caregiver Perceptions of Decision Making in Cancer Care

Abstract: Background. Shared decision making is a cornerstone of an informed consent process for cancer treatment, yet there are often many physician and patient-related barriers to participation in the process. Decisions in cancer care are often perceived as relating to a discrete, treatment decision event, yet there is evidence that decisions are longitudinal in nature and reflect a multifactorial experience. Objective. To explore patient and caregiver perceptions of the choices and decision-making opportunities withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, studies show that patient preferences for participation differ between cultures, 13 individuals 14 and through each individual’s phases of illness. 15 Moreover, a mismatch between patient preferences for participation and the actual participation is linked to negative patient experiences, such as frustrations, 16 burden, 17 and dissatisfaction with care. 13 This is at odds with other conceptual studies that, as already outlined, addressed the positive impact of patient participation.…”
Section: Revisiting Patients’ Perspectives On Person-centred Particip...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies show that patient preferences for participation differ between cultures, 13 individuals 14 and through each individual’s phases of illness. 15 Moreover, a mismatch between patient preferences for participation and the actual participation is linked to negative patient experiences, such as frustrations, 16 burden, 17 and dissatisfaction with care. 13 This is at odds with other conceptual studies that, as already outlined, addressed the positive impact of patient participation.…”
Section: Revisiting Patients’ Perspectives On Person-centred Particip...mentioning
confidence: 99%
“…Holdsworth et al 15 provide an example of such excesses of ‘forced-to participation’ in their study involving cancer patients’ perception of decision-making within which they were forced to take decisions about issues that they feel unqualified to deal with. The results showed that shared decision-making was uncomfortable for those patients, who preferred that a physician led the decision and who had difficulties in assessing the information presented to them.…”
Section: ‘Constrained Participation’ and Its Two Sub-conceptsmentioning
confidence: 99%
“…After initial discussion in the physician's office, the patient is given the IC for consideration of the risks, benefits, and required pretreatment testing, which can be burdensome and a deterrent to enrollment. 51,52 Telemedicine would allow this initial step to be conducted remotely. Additionally, opportunities to begin prescreening remotely by reviewing locally completed blood work, vital signs, and electrocardiograms would reduce delays and unnecessary travel especially for patients in remote areas.…”
Section: Remote Clinical Trial Education and Prescreeningmentioning
confidence: 99%
“…Collectively, the processed data could be used for retrospective, observational research including regulated studies on novel therapies. RWD from this platform (hereinafter “Invitae’s Ciitizen platform”) has already been used as natural history data to support a successful Investigational New Drug application for a novel treatment for pediatric patients with a severe form of epileptic encephalopathy [8].…”
Section: Introductionmentioning
confidence: 99%